Pengaruh Kualitas Pelayanan Dan Harga Terhadap Minat Beli Ulang (Studi Kasus Pada Coffee Shop di Pekalongan) - Gunawan Aji; Novi Safitri; Rizki Nurfita Wijaya; Wildan Dzikri Basilla; Nadia Nadia (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of service quality and price on repurchase intention at Coffee Shops in Pekalongan. This type of research is quantitative research. The test tools are Validity Test, Reliability Test and Hypothesis Test which includes T Test and F Test. The data collection strategy uses questionnaires to 30 respondents. SPSS application is a tool used for data analysis. This study found that service quality and price can affect customer satisfaction directly and there is an indirect effect on repurchase intention.